Challenges of the Implementation of Electronic Certificates in Indonesia and Malaysia: A Comparative Study - Anggriani, Reni; Rasmi, Audra Diana binti (Proceedings International Conference on Sustainable Innovation (ICoSI), 2025)
electronic certificates are a new thing and are a technological development carried out by the Ministry of Agrarian and Spatial Planning/National Land Agency (ATR/ BPN. Land is a very important need in human life. As the number of people increases, land never increases, so proof of land ownership becomes very important. Proof of land ownership is in the form of a certificate that is a sewn book in which there is physical and juridical data from a piece of land. Along with the times, there are new regulations that change certificates that were originally manual now to electronic certificates. There are doubts about electronic certificates, are they safe and have the same legal force as manual certificates? Electronic certificates are secure and have the same legal force as manual certificates. In Malaysia and Indonesia, electronic certificates have begun to be implemented. Electronic certificates are aimed at time efficiency and transparency